Effect of dynamic humeral centring (DHC) treatment on painful active elevation of the arm in subacromial impingement syndrome. Secondary analysis of data from an RCT. Issue 5 (23rd March 2013) - Beaudreuil, Johann; Lasbleiz, Sandra; Aout, Mounir; Vicaut, Eric; Yelnik, Alain; Bardin, Thomas; Orcel, Philippe
Abstract : Background: The physiotherapy dynamic humeral centring (DHC) aims to prevent subacromial impingement of rotator cuff tendons during elevation of the arm. The objective of the study was to determine whether DHC acts via an effect on subacromial impingement mechanism by assessing its effect on painful elevation of the arm in subacromial impingement syndrome. Methods: This is a secondary analysis of results of a randomised controlled trial of the effectiveness of DHC. Sixty-nine patients with subacromial impingement syndrome were prospectively included. Patients and the assessor were blinded to the study hypothesis and treatment, respectively. Patients underwent DHC or non-specific mobilisation as a control for 6 weeks in 15 supervised individual outpatient sessions with home exercises. Outcomes were pain-free range of motion and presence of painful arc of the shoulder, both in active flexion and abduction of the arm at 3 months. Results: At 3 months, pain-free range of motion, both flexion and abduction, was greater in the DHC group than in the mobilisation group. The number of patients with painful arc during flexion was decreased in the DHC group. Conclusions: DHC improves painful active elevation of the arm. We suggest that DHC may act via a specific effect on subacromial impingement mechanism.